Justification of the author’s methodology of emotional intelligence research - M. V. Butenko (Bulletin of Kharkiv National University of Internal Affairs)
Emotional intelligence is one of the new concepts in psychology, which is constantly being studied by many scientists. The article analyses the concepts of emotional intelligence, emotional competence and its structural components. The article considers various concepts of emotional intelligence of such scientists as P. Salovey, D. Mayer, D. Caruso, G. Gardner, R. Bar-On, S. Marcus, G. Dudchak, M. Mykolaychak. The article also analyses domestic concepts of emotional intelligence. As a result of the analysis of various scientific views on the concept of emotional intelligence and methods of its research, it has been made a decision to develop the author’s own psychodiagnostic test. The author has developed own test methodology for studying the emotional component, since there are no similar test methods in the national psychodiagnostics.